Predicting the effects of time pressure on design work. (12th May 2009) - Putkonen, Ari
The study describes an approach to simulate and predict the dynamic effects of mental workload (caused by time pressure) on design work. Project management, work ergonomics and studies about occupational health were used as a theoretical framework for the study. The results of the simulation indicate that the mental workload of workers has a significant effect on the Performance, Quality and Innovativeness (PQ&I) of design work and, consequently, on the lead time of the entire project. These effects are immediate or delayed. First, mental workload may have a positive effect on productivity in the short term, but a negative effect in the long term. Second, mental workload leads to delayed mental fatigue, which has a negative effect on quality and productivity in the long term. Finally, mental fatigue decreases work engagement, thus having a negative effect on the innovativeness of a design group. Conventionally, project planning has been based on the constant work efficiency of workers over the project timeline. This fails to give a realistic prediction about the resource needs and, thus, may lead to overly optimistic completion predictions. This study increases the understanding about the dynamic effects of time pressure on design work.